Is the Severity of the Penalty an Effective Deterrent? A Strategic Approach for the Crime of Tax Evasion - Bruno Chiarini; Elisabetta Marzano (Center for Economic Studies and ifo Institute (CESifo), 2016)
In order to analyze the severity of sentencing, and to show how the probabilistic interpretation of strategic behavior can be tricky, this paper uses the crime strategic model (inspection game) proposed by Tsebelis. This model shows that any attempts to increase the severity of punishment will alter the payoff of the individuals involved, leaving unchanged the frequency of violation at equilibrium. This result is misleading: payoffs are not independent and the crime game can not be simply read with mixed strategies. These are inconclusive on how the players act rationally. This is undeniably true for the crime of tax evasion, where the dishonest taxpayers are rational agents, motivated by the comparison of payoffs, considering the risk of breaking the law. Although an irreducible minimum of uncertainty remains, the Nash equilibrium in mixed strategies provides us with the necessary information on equilibria in pure strategies that will be played. In this context, tougher sentencing deters crime, although, as the Italian historical experience teaches, the necessary condition required is the certainty of punishment and the ability of the government to enforce it.
Keywords: C72; H26; K42; 330; crime game; tax evasion; deterrence; severity of punishment